THE IMPACT OF MINERALS IN MOUNTAIN AND FOOTLAND AREAS ON LANDSCAPES AND THEIR CLASSIFICATION - Nazarov Maksud Geldiyorovich; Fayzullaev Maksud Abdullaevich; Sultanov Shukhrat Adkhamovich; Navotova Dilnoza Ibragimovna (American Journals Publishing, 2025)
This article briefly analyzes the impact of mineral resources in mountain and foothill areas on landscapes. The impact of minerals in mountain and foothill areas on landscapes was also studied and their classification was developed.
Keywords: Igneous rocks, landscape, geological conditions, sedimentary rocks, effusive, karst, intrusive.